Pengaruh Fasilitas Dan Media Sosial Promosi Terhadap Keputusan Menginap - Tuwuh Adhistyo Wijoyo; Ray Octafian; Julian Andriani Putri; Sarah Nur Amalina; Azizah Naharia; Fadhill Ramadhan (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2023)
The importance of customer satisfaction has become a primary focus, with many companies investing in customer resources and continually seeking ways to enhance satisfaction. Promotional strategies through social media are an approach that can be adopted by tourism businesses such as accommodations to influence customer satisfaction. This research aims to explore the impact of social media and facility quality on customer satisfaction levels. The results of data analysis indicate that Facility Quality (X1) positively and significantly influences tourists' decisions to stay (Y). The influence of social media (X2) is also positive and significant on tourists' decisions to stay (Y). Together, facility quality (X1) and social media (X2) have a significant impact on tourists' decisions to stay (Y) at Glamping Mawar Camp, Bandungan.